Systemic vascular responses to increased intracranial pressure - Fitch, William (J Neurol Neurosurg Psychiatry, 1977)
Continued expansion of an artificial space-occupying lesion produced further increases in mean supratentorial and infratentorial pressures associated with increases in mean arterial pressure, heart rate, and systemic vascular resistance—the `Cushing' or systemic hypertensive response. These primary changes resulted in an increase in transtentorial pressure gradient and a decrease in arrhythmia index. Immediately before the onset of the systemic hypertensive response, supratentorial perfusion pressure was low, and the period of systemic hypertension did not appear to produce any worthwhile improvement in the perfusion pressure or in the blood flow in the supratentorial compartment. The studies demonstrated also that the systemic hypertensive response was a pre-terminal event and was followed rapidly by circulatory failure.